Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Which expression is equivalent to [tex]\( 4x^2 - 36x + 81 \)[/tex]?

A. [tex]\((4x+9)(4x-9)\)[/tex]

B. [tex]\((2x-9)(2x-9)\)[/tex]

C. [tex]\((2x-9)(2x+9)\)[/tex]

D. [tex]\((4x-9)(4x-9)\)[/tex]


Sagot :

To determine which expression is equivalent to [tex]\(4x^2 - 36x + 81\)[/tex], we need to factor the quadratic polynomial.

We start with the quadratic expression:
[tex]\[ 4x^2 - 36x + 81 \][/tex]

To factor this, we look for a common factor or use methods such as factoring by grouping. In this case, we can recognize that the quadratic can be written in the form [tex]\((ax + b)^2\)[/tex].

The steps to factor the quadratic are as follows:

1. Write the quadratic in the standard form: [tex]\( ax^2 + bx + c \)[/tex]
Here, [tex]\( a = 4 \)[/tex], [tex]\( b = -36 \)[/tex], and [tex]\( c = 81 \)[/tex].

2. Identify if it forms a perfect square trinomial:
A perfect square trinomial has the form [tex]\((mx + n)^2 = m^2x^2 + 2mnx + n^2\)[/tex].

3. Compare with the perfect square form:
We need [tex]\( m^2 = 4 \)[/tex], [tex]\( 2mn = -36 \)[/tex], and [tex]\( n^2 = 81 \)[/tex].

4. Solve for [tex]\( m \)[/tex] and [tex]\( n \)[/tex]:
[tex]\[ m^2 = 4 \Rightarrow m = 2 \text{ (since } m \text{ could also be } -2) \][/tex]
[tex]\[ n^2 = 81 \Rightarrow n = 9 \text{ (since } n \text{ could also be } -9) \][/tex]

5. Check the middle term [tex]\( 2mn = -36 \)[/tex]:
Substitute [tex]\( m = 2 \)[/tex] and [tex]\( n = -9 \)[/tex] into [tex]\( 2mn \)[/tex]:
[tex]\[ 2(2)(-9) = -36 \][/tex]

6. Rewrite the quadratic using [tex]\( m \)[/tex] and [tex]\( n \)[/tex]:
[tex]\[ 4x^2 - 36x + 81 = (2x - 9)^2 \][/tex]

Thus, the factored form of the quadratic expression [tex]\(4x^2 - 36x + 81\)[/tex] is:
[tex]\[ (2x - 9)^2 \][/tex]

Therefore, the corresponding answer from the given options is:
B. [tex]\((2x-9)(2x-9)\)[/tex]